Monitoring the agri-food system in Myanmar: Agricultural crop traders – April 2023 survey - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
To document changes in the mid-stream of Myanmar’s food value chains, a phone survey of commodity traders was conducted in April 2023 with a sample of 304 traders in 14 states and regions. Key Findings • Continuing trends from 2022, transportation disruptions and higher costs continue to be the most prevalent and the most impactful challenges facing crop traders in April 2023. Transport costs are 44 percent higher than a year ago and almost half of traders had difficulties accessing fuel, nearly doubling the share from one year prior. • In-person bank transfers have increased to 34 percent of crop sales, up from just 16 percent in 2022. However, average values of credit lent out to farmers and credit taken in by traders increased by more than 10 percent from 2022. • Lastly, crop prices, already high in 2022 after the start of the Russia-Ukraine War, have continued an upward trend, with Myanmar price increases outpacing global markets. However, local trading margins (as percentages of sales prices) have declined slightly since 2021, signaling continued competitiveness in crop trading. Looking Ahead • High crop prices may encourage investment in productive inputs and area expansions, hopefully leading to secure production in the 2023 monsoon. Conversely, higher prices are a negative for consumers, and continued difficulties and increased costs in transport will lead to wider price gaps between farmers and consumers and negative welfare effects. • For traders, high prices necessitate greater working capital. Improving access to capital and alleviating banking restrictions will further improve trade efficiency. • Lastly, export markets continue to be important for Myanmar’s agrifood system as important marketing channels that can stabilize prices from domestic demand shocks. Increased export demand can also increase domestic prices, which is a negative for consumers. Policies introduced to track exports more closely and bolster foreign currency reserves may add frictions to international crop trade that have knock-on effects through crop value chains.